COLLABORATION OF THE ETHNOBOTANY MATERIALS WITH THE ENVIRONMENTAL CARE ATTITUDE OF STUDENTS - Marlina, Reni; Irwanti, Muthia; Syamswisna, Syamswisna; Novita Oktavianti, Sri Andi (Universitas Tanjungpura, 2020)
One of the traditional utilization forms using diverse plants was a self-care ritual, which was anciently previously found in the tradition performed by women in the Qadriyah Palace of Pontianak Sultanate. The self-care ritual was aimed to treat either health-related problems or common diseases. Therefore, this ethnobotany study of the women self-care ritual was purposely implemented through a folding poster media in the tenth-grade sub-material of Senior High Schools, regarding the utilization of biodiversity in the field of cosmetics and medicines. The learning activity was collaboratively carried out with the teachers, so that students can recognize and preserve the varieties of beneficial plants in their environmental surroundings. The class selected as the subject of this study was class of X IPA 2. The collaborative learning process took place in two meetings; beginning with plan 1, performance 1, reflection 1; and plan 2, performance 2, and reflection 2 simultaneously in each meeting, with a duration of 90 minutes. The first cycle successfully implemented the ethnobotanic self-care-based folding poster media, previously performed by women in the Qadriyah Palace of Pontianak Sultanate’s environment, which had previously been validated by lecturers and teachers and was declared fit for use. Meanwhile, in the cycle 2, the media used was a flipbook. The results showed that collaborative learning using ethnobotany-based media can promote an environmental caring attitude amongst the tenth-grade students of SMAN 10 Pontianak.